Mais tempo menos historia. - Fernandes, Joao; Guerreiro, Antonio (Porto : Fundaçao de Serralves, 1996)
Agut, Pep ; Borland, Christine ; Carmona, Paulo ; Carneiro, Alberto ; Garrido, Patricia ; Maranha, André ; Mateus, Cristina ; Mora, Pedro ; Moraza, Juan Luis ; Parreno, Philippe ; Rainha, Ana ; Silva, Augusto Alves da ; Soares, Paula ; de Sousa, Ernesto ; Tropa, Francisco ; Vasconcelos, Joana
biografie
Mais tempo menos historia / More Time: Less History, Fundaçao de Serralves, Porto, July 18 - September 8, 1996
Portugees & Engels
boek